2021
DOI: 10.3390/d14010020
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Signals of Rhodoliths Beds since Bottom Trawling Ban in the SCI Menorca Channel (Western Mediterranean)

Abstract: One of the objectives of the LIFE IP INTEMARES project is to assess the impact of bottom trawling on the vulnerable benthic habitats of the circalittoral bottoms of the Menorca Channel (western Mediterranean), designated a Site of Community Importance (SCI) within the Natura 2000 network. The present study compares the epibenthic communities of four areas, subjected to different bottom trawl fishing intensity levels. The assignment of fishing effort levels was based on the fishing effort distribution in the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Although branched forms predominate in all sites, we observed small scale heterogeneity in the proportions of growth forms and even in the proportions of morphotypes. The heterogeneity observed agrees with previous studies in Mediterranean rhodolith beds (i.e, Bracchi et al 2022) and particularly in the Menorca Channel (Farriols et al 2022). The present study, together with preliminary results from ongoing molecular analysis,…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although branched forms predominate in all sites, we observed small scale heterogeneity in the proportions of growth forms and even in the proportions of morphotypes. The heterogeneity observed agrees with previous studies in Mediterranean rhodolith beds (i.e, Bracchi et al 2022) and particularly in the Menorca Channel (Farriols et al 2022). The present study, together with preliminary results from ongoing molecular analysis,…”
Section: Discussionsupporting
confidence: 92%
“…Due to their slow growth (of the order of 1 mm yr -1 , Blake et al 2007) rhodoliths exhibit exceptionally low renewal rates, which can result in slow recovery trajectories (Tauran et al 2020). However, some studies show evidence of recovery after relatively short periods of protection (3 to 6 years), while in other studies the benefits of protection may be inconclusive (Barberà et al 2017;Farriols et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…According to literature [6], literature [12] and literature [14], the ecological efficiency, economic efficiency and It can be seen from Tables 1 and 2 that the ecological efficiency, economic efficiency, and environmental efficiency of China's tourism industry in 2018-2021 are shown in Table 2. In document [6] and document [14], the calculation results of other years are completely different except that the efficiency values in 2019 and 2020 are 1.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…e research on the ecological efficiency of tourism industry cannot simply rely on the knowledge system and thinking of a single discipline. erefore, combined with the relevant theories and knowledge in the fields of tourism, management, industrial economics, regional economics, industrial ecology, and other disciplines, this paper Qiaozai's problems and countermeasures are systematically studied [14,15]. Scholars at home and abroad mainly pay attention to the management and utilization efficiency of tourist hotels, scenic spots, destinations, etc., while ignoring the analysis of ecological efficiency including resource consumption and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors studied the effects of different fishery management measures to preserve the rhodolith/maërl bed status; in particular, Consoli et al [21] indicated fishery spatial restrictions, such as no-take zones, as the more effective management tool to protect it rather than technical measures (e.g., increase of trawl net mesh size). Farriol et al [22] reported signals of recovery of rhodolith/maërl beds in areas closed to fishery, and demonstrated the effectiveness of no-take zone measures for the conservation of the habitat. The main conservation and management measures are found in the Barcelona Convention's Action Plan, where coralligenous and rhodolith/maërl assemblages, together with P. oceanica meadows, are indicated to require a granted legal protection, although it is not legally binding [23].…”
Section: Introductionmentioning
confidence: 99%